Who Gets to Be a Victim? How Media and Stereotypes Shape Perceptions of Sexual Crimes - Adomaitytė, Rasita (Kriminologijos studijos, 2024)
Crimes against a person’s freedom of sexual self-determination are complex and sensitive, violating fundamental rights and causing significant psychological harm. Public attitudes towards these crimes are often shaped by misconceptions and stereotypes, such as the “ideal victim” and “presumed perpetrator,” which bias perceptions. Nils Christie’s concept of the “ideal victim” highlights society’s preference for victims seen as innocent and vulnerable, fostering empathy only for those who fit this mold. Similarly, the “presumed perpetrator” stereotype frames offenders as deviant and powerful, attribution. When individuals deviate from these stereotypes, victim-blaming and bias can arise, simplifying attribution of blame. The analysis focuses on how the characteristics of victims and perpetrators influence the attribution of guilt within the context of Lithuanian society. The content analysis of mass media and criminal convictions explores how societal perceptions are shaped and how emphasising certain traits reflects ideologies surrounding “real rape” and the “ideal victim.” Additionally, qualitative semi-structured interviews examine the influence of these ideas on the attribution of guilt.
Keywords: stereotypes; Sexual violence; Social imaginaries; Media framing; Narratives